Does Popular Management Literature Lead Managers Up the Linguistic Garden Path? A Comparison of Popular Prescriptive ‘How-to’ Management Texts and a Descriptive Analysis of Workplace Interaction - Clifton, Jonathan (HERMES - Journal of Language and Communication in Business, 2010)
Popular management literature promotes the idea that certain management styles have a reﬂexive relationship with certain ways of talking. Consequently, by using prescribed ways of talking, certain management styles will be achieved and that, reﬂexively, certain management styles favor certain ways of talking. Using conversation analysis (CA) as a research methodology, this paper compares the prescriptive language advice of popular management literature as regards facilitation with video-taped data of naturally-occurring talk in a business meeting. Findings indicate that the intuitive insights on language use offered by popular management literature ignore the indexical nature of language use whereby the ‘meaning’ of any utterance and what that utterance does depends on its context of use. In short, such popular literature may lead managers up the (linguistic) garden path and may in fact be of little help in practice. The paper ends with a call for language advice in such literature to be more descriptive and less prescriptive.